Bounds on the Elastic Brittle solution in bodies reinforced with FRP/FRCM composite provisions. (January 2015) - Baratta, Alessandro; Corbi, Ileana; Corbi, Ottavia
Abstract: In the paper the behavior of composite-reinforced masonry structures is discussed. One focuses on the problem of the reinforced structure under different modeling of the basic material keeping into account possible strength in tension of the masonry material. Actually the presence of the reinforcement requires the development of a specialized treatment, that is presented in the paper, with the purpose of exploring the dependence of the solution on more or less refined hypotheses about the masonry material in the presence of reinforcement. The original set up leads to the formulation of new bounding theorems for masonry structures reinforced by composites, with the masonry possibly modeled by an elastic brittle assumption.